Analysis of Accounting Implementation in Textile Stores in Pekanbaru City District - Alifah, Vadhila; Aisyah, Farra (Riau International Conference on Economics, Business and Accounting, 2025)
The purpose of this study is to determine the suitability of the application of accounting applied by Textile Stores in Pekanbaru City District with the basic concept of accounting. This type of research is a qualitative descriptive study where the object of research is the Textile Store Business in Pekanbaru City District, the types and sources of data used in this writing are 1) Primary Data, where data is obtained directly from respondents through interviews and questionnaires. 2) Secondary Data, data obtained from agencies related to the management of Textile Businesses and from respondents obtained notebooks to record transactions. After being poured into a table and will be described descriptively so that it can be known whether Textile Store entrepreneurs in Pekanbaru City District have applied the basic concept of accounting. Based on the results of the discussion and research that has been done, it can be concluded: Textile Store entrepreneurs have applied the basic concept of accounting, namely the basic cash-based recording, but have not applied the concept of business continuity, time period, business entity concept and matching concept. So it can be concluded with the existence of a simple recording system and there are still many unused recording books. Textile Store Businesses in Pekanbaru City District have not applied accounting in accordance with the basic concepts of accounting.